2021
DOI: 10.18632/aging.203079
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel eight mutant-derived long non-coding RNAs signature as a prognostic biomarker for genome instability in low-grade glioma

Abstract: Long non-coding RNAs (lncRNAs) comprise an integral part of the eukaryotic transcriptome. Alongside proteins, lncRNAs modulate lncRNA-based gene signatures of unstable transcripts, play a crucial role as antisense lncRNAs to control intracellular homeostasis and are implicated in tumorigenesis. However, the role of genomic instability-associated lncRNAs in low-grade gliomas (LGG) has not been fully explored. In this study, lncRNAs expression and somatic mutation profiles in low-grade glioma genome were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…To compare the predictability of our GInLncSig model and the other three existing lncRNA-related signatures for LGG patients’ survival, we conducted ROC curve analyses using the same samples of the entire TCGA cohort. The other three lncRNA models were 8-lncRNA prognostic model documented by Maimaiti’s study (MaimaitiLncSig) ( Maimaiti et al, 2021 ), 5-lncRNA predictive model derived from Wang’s study (WangLncSig) ( Wang et al, 2020 ), and 6-lncRNA prognostic model reported by Lin’s study (LinLncSig) ( Lin et al, 2020 ). As outlined in Figure 9A , our GInLncSig model (AUC = 0.871, 0.851, and 0.723 for 1, 3, and 5 years) outperformed the MaimaitiLncSig (AUC = 0.743, 0.693, and 0.626 for 1, 3, and 5 years), WangLncSig (AUC = 0.866, 0.773, and 0.647 for 1, 3, and 5 years), and LinLncSig (AUC = 0.841, 0.766, and 0.721 for 1, 3, and 5 years) in predicting 1-, 3- and 5-year OS of LGG patients.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the predictability of our GInLncSig model and the other three existing lncRNA-related signatures for LGG patients’ survival, we conducted ROC curve analyses using the same samples of the entire TCGA cohort. The other three lncRNA models were 8-lncRNA prognostic model documented by Maimaiti’s study (MaimaitiLncSig) ( Maimaiti et al, 2021 ), 5-lncRNA predictive model derived from Wang’s study (WangLncSig) ( Wang et al, 2020 ), and 6-lncRNA prognostic model reported by Lin’s study (LinLncSig) ( Lin et al, 2020 ). As outlined in Figure 9A , our GInLncSig model (AUC = 0.871, 0.851, and 0.723 for 1, 3, and 5 years) outperformed the MaimaitiLncSig (AUC = 0.743, 0.693, and 0.626 for 1, 3, and 5 years), WangLncSig (AUC = 0.866, 0.773, and 0.647 for 1, 3, and 5 years), and LinLncSig (AUC = 0.841, 0.766, and 0.721 for 1, 3, and 5 years) in predicting 1-, 3- and 5-year OS of LGG patients.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs play a critical role in maintaining genomic instability ( Nair et al, 2020 ; Jianfeng et al, 2021 ). Increasing evidence has revealed the prognostic significance of GIRlncRNAs for cancers ( Fang et al, 2021 ; Liang et al, 2021 ; Maimaiti et al, 2021 ; Yan et al, 2021 ). Since NSCLC possesses a poor survival prognosis due to limited diagnosis and treatment ( Zappa and Mousa, 2016 ; Li C. et al, 2019 ), we developed a prognostic GIRlncSig to support the clinical stratification and treatment decision for NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…FLG-AS1 and AQP4-AS1 are two other DElncRNAs that were identified by our analysis. Dysregulation of FLG-AS1 was reported in some cancers, but the specific function and detailed mechanisms of FLG‐AS1 are still unknown 45 , 46 . A previous integrative analysis showed that FLG‐AS1 acts as a ceRNA in adipose tissue from obese individuals with type 2 diabetes 47 .…”
Section: Discussionmentioning
confidence: 99%